Prefrontal activation during dual-task seated stepping and walking performed by subacute stroke patients with hemiplegia - Nosaka, Shinnosuke; Imada, Ken; Saita, Kazuya; Okamura, Hitoshi (Frontiers in Neuroscience, 2023)
This study examined prefrontal cortex (PFC) activation during dual-task seated stepping and walking performed by subacute stroke patients with hemiplegia and evaluated the relationship between PFC activation, frontal lobe functions, and dual-task interference. Patients with functional ambulation category (FAC) scores ≤ 2 comprised the seated stepping task group. Those with FAC scores > 2 comprised the walking task group. There were 11 patients in the seated stepping task group (mean age, 63 years; age range, 55-73.5 years; 7 male and 4 female patients; time since stroke onset, 45.7±9.9 days) and 11 patients in the walking task group (mean age, 72 years; age range, 49.5-74.5 years; 7 male and 4 female patients; time since stroke onset, 57.5±18.3 days). Both groups completed the Frontal Assessment Battery (FAB), including the following three tasks: cognitive task (CT), normal seated stepping (NSS), and dual-task seated stepping (DTSS). The walking task group completed the following tasks: CT, normal walking (NW), and dual-task walking (DTW). The CT was a letter fluency task; this letter fluency task was simultaneously performed during seated stepping (DTSS) and walking (DTW). Changes in the oxygenated hemoglobin (O2Hb) concentration and deoxygenated hemoglobin concentration during the tasks were measured using near-infrared spectroscopy (Pocket NIRS HM; Dynasense Inc., Japan). The number of steps, walking speed, and percentage of correct responses to the CT were recorded. The results showed that DTSS activated the PFC significantly more than performing a single task and that NSS was associated with a significantly higher difference in the hemoglobin concentration when compared to that associated with the CT, which was a single task. In the walking task group, PFC activation was significantly higher during DTW, NW, and CT (in that order), and O2Hb concentrations were significantly higher in the contralesional hemisphere than in the ipsilesional hemisphere during all tasks. Associations between PFC activation, FAB performance, and dual-task interference in the seated task group indicated significant positive correlations between PFC activation and cognitive performance with dual-task interference and between FAB performance and cognitive performance with dual-task interference. DTSS may be an effective means of activating the PFC of patients with difficulty walking.